THE EFFECTIVENESS OF USING PORTFOLIO IN ASSESSING THE ENGLISH LANGUAGE SKILLS AT SMPN 2 SUSOH - Mawardah, Mawardah; Zuhri Efendi (Yayasan Nusantara Hasana Berdikari, 2025)
This study examines how well portfolios work at SMPN 2 Susoh as a tool for evaluating students' English language competency. Assessment plays a crucial role in the learning process, and in order to maximize student learning results, teachers must administer tests that are consistent with learning objectives. This study aims to evaluate the efficacy of portfolios in evaluating SMPN 2 Susoh students' English language competency. Research of this kind is descriptive and qualitative. The researcher chose one teacher who employed portfolio evaluation to gauge students' writing abilities using the purpose sampling technique. During the odd semester of 2024–2025, in-depth interviews and observation were used to gather data. The results demonstrated that, in the early stages of the portfolio review process, the English teacher successfully conveyed to the students the goal of the portfolio. An engaging classroom environment is created when teachers clearly explain the learning objectives and evaluation criteria, inspiring students to take an active role in their education. The study also highlights the value of professors providing students with systematic support in creating their portfolio content, which includes compilations of their work, feedback on drafts, and personal remarks. Portfolios are a useful tool for skill improvement as well as assessment.